Mélancolie spartiate. 300 ou la réactivation du mythe de Léonidas pour mobiliser la société contre le déclin de l’Occident - Vivien Barrière; Jean Hedin (Frontière·s)
In 2007, Zack Snyder made a movie about Leonidas and the 300 Spartans who fell at Thermopylae to the Persian forces of Xerxes. The movie was inspired by a graphic novel by Frank Miller, which presented a distorted vision of Sparta as the mother of American democracy and a model for countering expansionist and liberticidal projects from the Middle East. Even more than the original comic book, the film, made in the USA of G.W. Bush, still traumatized by the attacks of 11 September 2001 and obsessed by his desire for revenge, is a genuine attempt to mobilize American society, and more broadly Western societies, against the existential threat posed by the conquering East to Westerners who are losing ground. This virile, warlike, eugenicist Sparta portrayed by F. Miller as the ideal ancient city, has seduced identitarian, xenophobic and declinist circles in France and abroad.